2001
DOI: 10.1159/000046720
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of the Effect of Infant Feeding on Celiac Disease

Abstract: Aims: The aim of this study was to investigate the association between the duration of breast-feeding and the age at the first gluten introduction into the infant diet and the incidence and age at onset of celiac disease. Methods: In a case-control study, 143 children with celiac disease and 137 randomly recruited gender- and age-matched control children were administered a standardized questionnaire. Multivariate-adjusted odds ratios (OR) as estimates of the relative risk and corresponding 95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
96
2
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 18 publications
3
96
2
4
Order By: Relevance
“…10 However, 2 other studies from Sweden and Germany found no association between timing and risk for CD, suggesting that there might be differences in the risk factors by country of residence. 7,24 Because our study cohort comprised children from 4 different countries, we tested for this heterogeneity by applying a model that included the interaction between age at gluten introduction and country, and it was not statistically significant (data not shown), suggesting that the associations did not vary by country. We adjusted for country of residence in our analyses to remove possible effects such as country-specific infant feeding practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 However, 2 other studies from Sweden and Germany found no association between timing and risk for CD, suggesting that there might be differences in the risk factors by country of residence. 7,24 Because our study cohort comprised children from 4 different countries, we tested for this heterogeneity by applying a model that included the interaction between age at gluten introduction and country, and it was not statistically significant (data not shown), suggesting that the associations did not vary by country. We adjusted for country of residence in our analyses to remove possible effects such as country-specific infant feeding practices.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies hypothesized that the age at first introduction to gluten could influence the onset of the disease. [6][7][8][9][10][11] Others claim that breastfeeding and its interaction with gluten during weaning could reduce the risk for CD. 12,13 Today, the general recommendation is to introduce small amounts of gluten while the infant is still breastfed, preferably between 4 and 6 months of age.…”
mentioning
confidence: 99%
“…Greco et al compared children breast fed for at least 90 days with children breast fed for more than 90 days, 22 Peters et al compared children breast fed for more than 2 months with those breast fed for less than 2 months, 4 and Auricchio et al compared children breast fed for more than 30 days with those breast fed for less than 30 days. 5 Falth-Magnusson et al 23 and Ascher et al 6 compared the median time of both exclusive and partial breast feeding in cases and controls.…”
Section: Duration Of Breast Feedingmentioning
confidence: 99%
“…3 They found that the risk of the disease was reduced in children if they were breast feeding at the time of introduction of dietary gluten. Peters et al 4 and Auricchio et al 5 also showed that breast feeding was associated with a reduced risk of developing childhood CD. While these and other observational studies have suggested that breast feeding might reduce the risk of CD, at least one study did not find such an association.…”
mentioning
confidence: 97%
“…Риск, ве роятно, обусловлен наследственной тенденцией взаимодействия с различными факторами окружа ющей среды, включающими питание, распростра ненность гастроэнтерита и наличие грудного вскармливания [11]. Результаты нескольких иссле дований показывают протективные свойства груд ного вскармливания в отношении целиакии в дет ском возрасте [12][13][14].…”
unclassified